Subcellular calcium patterns in ventricular myocytes - Veasy, Joshua (2018)
Understanding the biology and mechanisms as to how the heart contracts has long been a point of interest for biologists and mathematicians alike. Since inconsistent beating of the heart has been linked to multiple pathological conditions, research into this area has been extensive but we still only have some of the answers. One of the key findings over the last century has been the role of calcium in activating the machinery within the heart that drives contraction. Further studies have shown that when calcium is mishandled by the heart's myocytes, it can lead to some of these pathological conditions. Since such discoveries a major point of research into the heart has focused on the possible avenues that calcium mishandling can occur.